PENGARUH PENGGUNAAN FACEBOOK TERHADAP INTERAKSI SOSIAL REMAJA DI SMKN PERTANIAN TERPADU PROVINSI RIAU - Adinda Elsa Saputri; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Facebook is very influential on adolescent social interaction seen from a high level of adolescent motivation in using this facebook. The research aims to determine the effect of using facebook to adolescent social interaction in the play facebook. Metode study is correlational nature with quantitative approach that compares motivation teenagers using facebook and social interactions play facebook. Sampel used in this study is the Integrated Agricultural SMKN Riau Province consists of 100 class X and class XI 79 Random selected Sampling. The results of analysis data can be concluded that the use of facebook influence on adolescent social interaction with significant value Sig.0.001 of <0.05 and views of the value of the average score Motivation teenagers using facebook as much as 67 respondents with a percentage of 37.4% and the Social Interaction 39 respondents with a percentage of 21.8% .With thus seen a significant difference between the use of facebook with Social Interaction teens in play facebook.Keywords: Facebook, Social Interaction, teenagers